KOMPARASI KERAGAMAN JENIS BURUNG-BURUNG DI TAMAN NASIONAL BALURAN DAN ALAS PURWO PADA BEBERAPA TIPE HABITAT - W. Widodo (The East Java Biological Society, 2009)
This research was conducted to compare the species diversity of birds in the Baluran and Alas Purwo National Parks (NPs), East Java Province. The research was done on April 2006. The IPA method was used in this bird’s survey. The parameters of the observation were species numbers (S), the total number of each species (n), the total number of all of species (N), the Shannon diversity (H) and the equitability or evenness indices (J), the Simpson diversity (D) and the equitability indices (E). The results showed that Alas Purwo NP has more species numbers than Baluran NP, i.e. 56: 50 species. The highly value of species diversity in the Baluran NP was found on the natural forests habitat, namely 40 species with index values of H’ = 3.27. The highly value of species diversity in the Alas Purwo NP was found on the production plant forests habitat (Tectona grandis), namely 46 species with index values of H’ = 3.33. The Columbidae and Pycnonotidae families were found more abundant in two national parks area. The values of their relative abundance were 17.9% and 11.0%, respectively. By “t” test knows that species diversity (S) have no significant to the H and D diversities indices and the J and E equitabilities indices (P > 0.05). Nevertheless, there appears to be a strong and positive correlation between the species diversity (S) and to the value of H and D indices (P < 0.05, db = 3), with r-value = 0.9204 and r = 0.9031 respectively. In while, the value of S to the E indices are negative correlation highly significant (P < 0.01; db = 3) with r = –0.9785. However, the species diversity value is no correlation significant to J indices with r = –0.3092.